Multiple roles of apolipoprotein B mRNA editing enzyme catalytic subunit 3B (APOBEC3B) in human tumors: a pan-cancer analysis - Jiacheng Wu; Ni Li; Linwen Zhu; Dawei Zhen; Mengqi Li; Hang Chen; Mengmeng Ye; Yiqin Wei; Guofeng Shao (BMC Bioinformatics, 2022)
Abstract Although there have been some recent cell and animal experiments indicating that expression of the gene encoding apolipoprotein B mRNA editing enzyme catalytic subunit 3B (APOBEC3B) is closely related to cancer, it still lacks pan-cancer analysis. Here we analyzed the potential carcinogenic role of APOBEC3B in 33 tumors based on The Cancer Genome Atlas (TCGA). APOBEC3B was highly expressed in most tumors and weakly expressed in a few. Differences in expression level were significantly correlated with the pathological tumor stage and prognosis of affected patients. The high-frequency APOBEC3B changes were principally mutations and amplifications in some tumors, such as uterine corpus endometrial carcinomas or cutaneous melanomas. In testicular germ cell tumors and invasive breast carcinomas, APOBEC3B expression and CD8+ T lymphocyte counts were correlated. In other cancers, such as human papilloma virus (HPV)-related head and neck squamous cell carcinomas or esophageal adenocarcinomas, there was also cancer-associated fibroblast infiltration. The APOBEC3B enzyme acts in the mitochondrial respiratory electron transport chain and in oxidative phosphorylation. This first pan-cancer study provides a comprehensive understanding of the multiple roles of APOBEC3B in different tumor types.